ANALISIS PENAMBAHAN HARGA PADA SISTEM PEMBAYARAN CASH BERTAHAP PERSPEKTIF JUMHUR ULAMA DAN ULAMA KONTEMPORER - Ines Prasheila Kusmastuti (KASBANA, 2024)
Gradual cash payments provide many conveniences for the community. Buyers who do not have funds can purchase goods with a down payment and the remainder is paid according to the agreed time. The problem is that there is an additional price charged to buyers and this has the potential to include usury which is prohibited. This research aims to analyze the addition of prices in the gradual cash payment system from the perspective of a number of ulama and contemporary ulama. The research method used in this research is normative by collecting data through literature study. The results of this research show that adding prices to the gradual cash payment system according to Jumhur ulama is permissible and does not constitute usury because it is not aimed solely at making a profit. This addition also cannot be categorized as gharar because there is an agreement between both parties. On the other hand, contemporary scholars differ regarding the permissibility of adding prices to gradual cash payments. Scholars who allow it assume that price increases are not usury because they are done freely, while scholars who prohibit it assume that price increases are usury.